2016
DOI: 10.1021/acs.energyfuels.6b01720
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transportation and Enhanced Coalbed Methane Recovery Processes in Deep Coal Seams: A Review

Abstract: Coalbed methane (CBM) is a potential green energy supply for addressing the worldwide energy crisis. However, the recovery of economically viable amounts of methane requires the application of production-enhancement techniques. The greater effectiveness of enhanced coalbed methane (ECBM) recovery compared to traditional pressure depletion and hydraulic stimulation techniques has been identified in terms of higher CBM recovery with minimal pollution risk and the ability to contribute to CO2 sequestration. Gas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
84
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 98 publications
0
84
0
2
Order By: Relevance
“…The fluid‐solid model was used to rationalize and explain the trends of experimental data. Due to the complex coupling responses of ternary gases, numerical simulations are assumed to be an effective method to represent the process of ECBM recovery by gas injection . Sayyafzadeh et al optimized the injected mixture with less CO 2 by a semisynthetic simulation model, which improved methane recovery ratio by 21.1% comparing to natural depletion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid‐solid model was used to rationalize and explain the trends of experimental data. Due to the complex coupling responses of ternary gases, numerical simulations are assumed to be an effective method to represent the process of ECBM recovery by gas injection . Sayyafzadeh et al optimized the injected mixture with less CO 2 by a semisynthetic simulation model, which improved methane recovery ratio by 21.1% comparing to natural depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex coupling responses of ternary gases, numerical simulations are assumed to be an effective method to represent the process of ECBM recovery by gas injection. 34,35 Sayyafzadeh et al 31 optimized the injected mixture with less CO 2 by a semisynthetic simulation model, which improved methane recovery ratio by 21.1% comparing to natural depletion. Although some important factors, such as heat transfer and coal permeability, were ignored, the numerical simulation of mixed gas injections has provided a useful theoretical basis for coalbed methane recovery enhancement.…”
mentioning
confidence: 99%
“…The relatively clean-burning nature of CBM has drawn much attention for its potential to provide energy source to a world in need of clean energy supplies. Enhanced coalbed methane (ECBM) technology, which implemented by injecting CO 2 (CO 2 -ECBM) or N 2 (N 2 -ECBM) or flue gas into the coal seam to replace the adsorbed CH 4 , has become a promising technique to recover CBM, with less environmental pollution and higher recovery rates and CO 2 -ECBM has the additional benefit of immobilizing large amounts of CO 2 , which is the main greenhouse gas responsible for global warming [9,10]. However, during this process, the adsorption/desorption of gas/fluids create significant changes in the mechanical properties of coal mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, during this process, the adsorption/desorption of gas/fluids create significant changes in the mechanical properties of coal mass. Changes in coal strength properties may occur due to gas and water sorption during the ECBM process and this leads to the reduction of coal seam permeability and recovery rates [9]. Therefore, an investigation of the changes of coal mechanical property associated with adsorbate type and content is of great significance, not only for a better understanding of the outburst phenomenon during coal mining but also for a full appreciation of coal seam permeability changes, the key factor controlling CBM recovery during the ECBM process.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption capacity of methane decreases by approximately 19%, 32% and 45% for coals at micro-pore with sizes of 0.7-0.9 nm, 1.0-1.3 nm and size that larger than 1.4 nm respectively. Although many researchers have pointed out the effects of temperature on gas sorption, a theoretical presentation based on experiments that can concisely and usefully describe the effects is still lack.Change of reservoir temperature causes a succession of interactions to CBM seepage behavior and the evolution of coal permeability [25][26][27]. Wang et al [28] found that the evolution of coalbed permeability with increasing temperature may be divided into two stages: coal permeability decreases due to the internal swelling of coal matrix at the first stage and increases at the domination of rising gas pressure.…”
mentioning
confidence: 99%